Anti-HLA-A2 antibody-enhancement of peptide association with HLA-A2 as detected by cytotoxic T lymphocytes. - Bodmer, H; Ogg, G; Gotch, F; McMichael, A (1989)
Most cytotoxic T lymphocytes (CTL) not only recognize epitopes of viral or other foreign proteins in association with class I major histocompatibility complex (MHC) molecules, but also recognize target cells sensitized with short synthetic peptides representing the epitopes. There is increasing evidence that these synthetic peptides associate with the class I molecule both at the cell surface and intracellularly. We have now investigated the effect of a monoclonal antibody specific for HLA-A2 and HLA-B17 (B57/58) molecules (antibody MA2.1)3 on the sensitization of target cells with peptide for lysis by HLA-A2-restricted CTL. Previously, anti-HLA class I monoclonal antibodies have been shown to inhibit the recognition of target cells, infected with influenza A virus, by virus-specific CTL. We find, however, that target cells treated with MA2.1 antibody can be sensitized with peptide for CTL lysis much more rapidly than untreated cells, or at greater than 100-fold lower peptide concentration than that required for sensitization of untreated cells. This implies that the antibody, which is believed to bind to one side of the peptide-binding groove, directly affects the binding of peptide to the HLA-A2 molecule at the cell surface.